2018
DOI: 10.1002/jcb.27315
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: microRNA‐590‐5p targets transforming growth factor β1 to promote chondrocyte apoptosis and autophagy in response to mechanical pressure injury

Abstract: This study aimed to investigate the role of miR-590-5p in chondrocyte apoptosis and autophagy in response to mechanical pressure injury in vitro, as well as to elucidate its regulatory mechanism in the pathogenesis of osteoarthritis. We applied mechanical pressure of 10 MPa to chondrocytes for 60 minutes to establish the chondrocyte model of experimentally induced mechanical injury. We then investigated the expression of miR-590-5p in the injury model and the effects of miR-590-5p dysregulation on the expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…For example, Lian et al [ 27 ] showed that miR-128a represses chondrocyte autophagy and exacerbates knee OA by disrupting autophagy related 12 gene. Wang et al [ 28 ] indicated that mR-590-5p targets transforming growth factor β1 to promote chondrocytes apoptosis and autophagy in response to mechanical pressure injury. Yu et al [ 29 ] demonstrated that inhibition of miR-126 protects chondrocytes from IL-1β induced inflammation via up-regulation of Bcl-2.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Lian et al [ 27 ] showed that miR-128a represses chondrocyte autophagy and exacerbates knee OA by disrupting autophagy related 12 gene. Wang et al [ 28 ] indicated that mR-590-5p targets transforming growth factor β1 to promote chondrocytes apoptosis and autophagy in response to mechanical pressure injury. Yu et al [ 29 ] demonstrated that inhibition of miR-126 protects chondrocytes from IL-1β induced inflammation via up-regulation of Bcl-2.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that there may be a common regulatory factor between autophagy and apoptosis. In the model of focal cerebral ischemia and ischemic injury, Beclin 1 may be involved in the activation of caspase-3, and the anti-apoptotic protein Bcl-2 binds to Beclin 1 to block autophagy (Ciechomska et al, 2009; Yang et al, 2017; Ding et al, 2018; Wang J. et al, 2018). In the present study, we established a rat model of CCH and took samples at different timepoints of resveratrol treatment.…”
Section: Discussionmentioning
confidence: 99%
“…A study by De Palma et al [56] reported that mechanical loading downregulated MIR-155 and MIR-181a in OA cartilage and activated the NF-κB pathway. Mechanical loading increased MIR-590-5p expression and activated TGF-β thereby enhancing chondrocyte apoptosis and autophagy [57]. Overloading activates the IL-1 β pathway and ADAMT5 and upregulates MIR-145 to promote ECM degradation [16].…”
Section: Microrna and Osteoarthritismentioning
confidence: 99%